EFEKTIFITAS ANESTESI SPINAL TERHADAP HEMODINAMIK PASIEN SECTIO CAESAREA - Khoirul Umamah; Henry Sudiyanto; Dwiharini Puspitaningsih (MEDICA MAJAPAHIT, 2025)
Caesarea section surgery uses a spinal anesthesia technique that has many advantages including a faster drug effect, deeper sensory and motoric blockade, a simple technique, minimal impact on the baby, and a small risk of anesthetic drug toxicity. This study is aimed at identifying the relationship and changes in spinal anesthesia to the hemodynamics of patients undergoing a caesarean section at the Central Surgery Facility of Bhayangkara Hospital H.S. Samsoeri Mertojoso Surabaya. This research is a correlation study with the method used, i.e. with a quantitative method with a cross - sectional approach. The independent variables used are spinal anesthesia and the dependent variables that are used are blood pressure, MAP, and pulmonary pressure. The results of the study showed a pre-induction hemodynamic change with the 5th minute after induction. In the 10th and 15th minutes tended to indicate normal state. In correlation tests showed that there was a relationship between the time of pre-induction administration and the 5-th minute of induction in the systolic blood pressure variables and MAP values, but in diastolic and pulmonary blood pressure there was no relationship or correlations at the time. Correlation test results indicated a positive direction of the relationship. The changes before and after the hemodynamics of a caesarean section are caused by the administration of anesthetic drugs, so it can be said that spinal anesthesia has been associated with the haemodynamic changes of a Caesarea section.